Evaluation of Student Learning Outcomes in Problem-Based Learning: Study of Its Implementation and Reflection of Successful Factors - Erpin Evendi; Ni Nyoman Sri Putu Verawati (Postgraduate, University of Mataram, 2021)
Behind the successful of teaching using the problem-based learning (PBL) model, -in our best knowledge- it seems that the factors that make its implementation successful in the classroom have not been mentioned, this is related to the purpose of improving student learning outcomes. For this reason, the study of the implementation of the PBL model needs to be explored further. Specifically, the aim of our current study is to evaluate student learning outcomes in implementing the PBL model and reflecting on the learning process using this model. This study is a Classroom Action Research (CAR), which is an examination of activities or actions that are intentionally conducted in a teaching. In the context of this study, the observation is carried out by evaluating student learning outcomes, while the activity or action that is carried out is Problem-Based Learning (PBL) which is carried out in two learning cycles. The subjects for implementing the PBL model were 21 students in an Islamic school (MTs NW - equivalent to Junior High School) in Central Lombok, Indonesia. Quantitative and qualitative approaches were used to analyze student learning outcomes and the learning process using the PBL model. The results of the study showed that there was an increase in student learning outcomes from the first cycle to the second cycle. Individual and classical completeness has been achieved in accordance with predetermined criteria. Finally, we recommend the use of the PBL model for the purpose of improving student learning outcomes. In the PBL model, the role of motivation, cues, encouraging active student participation, and the use of scaffolding are important aspects in the successful implementation of the PBL model